Literature Review: Factors Associated with the Incidence of Diabetic Retinopathy in Patients with Type II Diabetes Mellitus - Amalia, Mutiara; Yanti, Andi Kartini Eka; Nurtania, Ariyanie (Journal La Medihealtico, 2025)
Diabetes Mellitus (DM) type II is a metabolic disorder caused by insulin resistance in muscle and liver cells, as well as pancreatic beta cell failure. Diabetic retinopathy is one of the diseases that is a microvascular complication of the retina due to chronic hyperglycemia in patients with Type II DM. Chronic hyperglycemia in patients with type 2 DM can change the physiology and biochemistry of cells, resulting in endothelial damage. In this condition, various biochemical pathways are activated, and this affects the occurrence of 4 pathophysiologies of diabetic retinopathy. Several risk factors suspected of triggering diabetic retinopathy are age, duration of disease, poor blood sugar control or hyperglycemia and blood pressure, dyslipidemia, hyperviscosity, kidney failure, anemia, and smoking. Blood sugar control is the most dominant risk factor for diabetic retinopathy among other factors in patients with type II DM. Based on the background, the author is interested in conducting research on risk factors that influence the incidence of diabetic retinopathy. The purpose of this study was to determine the risk factors that influence the incidence of diabetic retinopathy. The research conducted was a Literature Review with a Narrative Review design. Based on the search results, 7 relevant articles were obtained for use in this Narrative Review. The conclusion is that the risk factors suspected of causing diabetic retinopathy include the duration of diabetes mellitus, uncontrolled blood sugar levels, and Type II DM patients with hypertension or dyslipidemia.